Understanding the changes in the conceptualization of autism spectrum disorder for educational inclusion - Sandoval, Carmen (2021)
The article presents the results of a literature review that explains the changes in the conceptualization of autism spectrum disorder (ASD) during the last century, from Bleuler studies to the present day. The bibliographical research was done during the months of October 2020 and April 2021. The analysis shows ASD concept has changed all over time. Initially it was understood from a psychiatric level and it is currently recognized as a neurodevelopmental disorder. This research also details the main characteristics and early warning signs of Austism Spectrum Disorder (ASD) in early childhood from the current point of view which frames it within the neurodevelopmental disorders and points out that it has a dimensional approach. The information provided by this research is oriented towards the main agents involved in the education of children diagnosed with ASD, so that it can be disclosed among teachers and interested people in order to identify the early signs and symptoms before the first three years of life.